Darina
Answered

Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

f(x)=x^3+ax^2+bx+3 where a and b are constants. bx Given that when f (x) is divided by (x+2) the remainder is 7, (a) show that 2a-b=6 Given also that when f (x) is divided by (x-1) the remainder is 4. (b) Find the value of a and the value of b
I don't know how solve it :(((((((


Sagot :

Part I - First synthetic division

You need to use synthetic division to come up with an expression for a and b:

(x + 2) is a factor, and the remainder is 7, so we can draw a synthetic division table...

coefficients = 1 for X^3; A for X^2; B for X^1; and 3

-2  |        1          A            B                 3
     
                        -2        -2(A-2)          4(A-2)-2B
 
            1        (A-2)    -2(A-2)+B      4(A-2)-2B + 3  
                            
                                    Remainder = 7

So...

4(A-2)-2B + 3 = 7

4 * (A - 2) - 2B + 3 = 7

4A - 8 - 2B =  4

4A - 2B      = 12

2A - B = 6
Proved

-------------------------------------------------------------------------------------------------------------------
Part II - Second Synthetic Division

We draw another synthetic division table, this time with (x - 1), so the number on the left hand side will be +1

1  |        1          A            B                 3
     
                        1         (A+1)         A+B+1
 
             1      (A+1)      A+B+1       A+B+4 
                            
                                    Remainder = 4

So... 

A + B + 4 = 4

A + B = 0

A = -B

-------------------------------------------------------------------------------------------------------------------
Part III - Solving for A and B with our two simultaneous equations

We know that A = -B and we also know that 2A - B = 6

Since we know that A is equal to -B We can substitute in for -B, to get:

2A - B = 6

Therefore...

2A + A = 6

3A = 6

A = 2

Again, as we know that A = -B, and as we have found that A = 2, we can see:

A = -B

Therefore...

2 = -B

B = -2

So our final answer is A = 2, B = -2

Hopefully this answer is more useful than the last one, and isn't so confusing!

We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.